FORMS AND REGULATION OF THE PLACEMENT OF CHILDREN DEPRIVED OF PARENTAL CARE IN INTERNATIONAL FAMILY LAW (Neo Scientific Peer Reviewed Journal, 2025)
The article examines key international legal standards and protection mechanisms for children deprived of parental care, as well as the main forms of their placement — adoption, foster care, guardianship, and institutional measures. Special attention is devoted to the provisions of the 1989 Convention on the Rights of the Child, the Hague instruments on cross-border aspects, and regional approaches. The paper explores the correlation between universal standards and national-cultural practices (including kafala), while analyzing examples of foreign practice and national regulation, with particular focus on the Republic of Uzbekistan. The author concludes that further deinstitutionalization and strengthening of family-based care remain essential to ensuring the child’s best interests.